Emergence from Anaesthesia in Supine versus Prone Position in Patients Undergoing Lumbar Laminectomy: A Study of 60 Cases. (30th August 2012) - Goyal, Priyanka; Nagrale, Manda; Joshi, Sandeep
Abstract : Background . Emergence in supine position in patients undergoing surgery in prone position leads to tachycardia and hypertension, coughing, and the loss of monitoring when patients are rolled to supine position at the end of surgery, aim of this prospective randomized trial was to study whether prone emergence causes less hemodynamic stimulation, coughing, and monitor disconnection compared to supine emergence in patients undergoing lumbar laminectomy. Patients and Methods . This study was conducted on 60 patients who underwent Lumbar laminectomy in prone position. Patients were anaesthetized using injected fentanyl 2  μ g kg −1, midazolam 0.1 mg kg −1, and thiopentone 5–6 mg kg −1 and vecuronium bromide. At the end of surgery patients were randomized into prone or supine group of 30 each. Supine group patients were rolled back and prone were left undisturbed. Extubation was done after complete reversal of neuromuscular block. Heart rates and MAP were noted at various points of time. Coughing, vomiting, monitor disconnection if any. Results . Mean arterial pressure and heart rate were significantly higher in supine patients as compared to prone patients before and after extubation ( P value < 0.05). Incidence of coughing, vomiting and monitor disconnection was highly significant in prone group than in supine group. Conclusion . Emergence and extubation in prone position can be safely performed in selected group of patients undergoing surgery in prone position.